Risk and Vulnerability in Nepal : Findings from the Household Risk and Vulnerability Survey - Walker, Thomas; Kawasoe, Yasuhiro; Shrestha, Jui (World Bank, Washington, DC, 2020)
This report summarizes the findings of a unique panel survey of rural households in Nepal, conducted between 2016 and 2018 by the World Bank with financing from the UK Department for International Development (DfID). The survey covered six thousand households in rural and peri-urban areas nationwide. The objective of the survey was to better understand the exposure of households to major natural and socio-economic shocks, their means of coping with these shocks, and the impact of shocks on household welfare. While most households appear to be able to withstand a range of smaller shocks to assets and income, larger and more covariate shocks continue to pose a major risk to household assets, food security and overall welfare. These effects persist for up to two years following the shock. The authors findings point to the importance of having established formal social assistance to help the chronically poor build their resilience and assist other households that are normally non-poor to cope in the event of major shocks.